Antimicrobial activity of essential oils on pathogenic fungi - Daniele Aparecida do Couto (Revista Agrogeoambiental, 2017)
Since the induction of chemical defensives in agriculture, human beings have suffered from our own actions, caused by the indiscriminate and abusive use of those substances; therefore, researches have been motivated to look for alternative ways, aiming to use plant inputs to control pathogenic agents in agriculture. As the essential oils from the species Eucalyptus globulus (eucalyptus), Callistemon viminalis (weeping bottlebrush), Cymbopogon winterianus (citronella grass) and Tetradenia riparia (misty plume bush) have proved effectiveness and an immense applicability, this research studied the use of those essential oils, aiming the effectiveness against plant pathogens. The plants were collected from Universidade do Vale do Sapucaí, Pouso Alegre (MG). The fungi’s samples belong to the mycology collection from the institution and the tests were based on the mycelial development comparison of the control fungi on the dishes with essential oils. Notice that the inhibition caused by the oils over fungi’s mycelial developing and the analysis of the data have been made through Turkey’s statistic. From the data analyzed, it was possible to realize that the citronella’s grass essential oil was efficient to control the mycelial development of fungi analyzed, followed by, in order of efficiency, the eucalyptus oil, the weeping bottlebrush oil and the misty plume bush oil.